The Effectiveness of Rational Emotive Behaviour Therapy (REBT) Group Counselling in Enhancing Students’ Self-Confidence: A Literature Review - Saragih, Tiara Nova Andre; Darmayanti, Nefi (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2024)
This research aimed to prove the role of group counselling using the Rational Emotive Behaviour Therapy (REBT) approach in increasing students' self-confidence. It discussed literature regarding the effectiveness of group counselling with the REBT approach in enhancing students' self-confidence. The research method used was a qualitative approach with a systematic literature review method. A systematic literature review was a research process that identified, evaluated, and interpreted relevant research related to research questions, certain topics, or phenomena that were being studied. The results of this research showed that the effectiveness of group counselling using the REBT approach in increasing students' self-confidence was significant. By employing various evaluation methods such as self-confidence scales, behavioural observations, student interviews, measuring stress and anxiety levels, and monitoring academic achievement, this research succeeded in measuring significant changes in students' self-confidence. The effectiveness of REBT was evident in changes in students' thinking patterns and behaviour, leading to increased learning confidence. Key success factors, such as changes in group member behaviour, increased student self-understanding, and support among group members, made important contributions to achieving the goals of group counselling.